IDENTIFIKASI POLA TIDUR GENERASI Z (GEN-Z) MENGGUNAKAN ALGORITMA KLUSTERISASI K-MEANS - Annisa, Riski; Rahayuningsih, Panny Agustia; Anna, Anna; Hidayana, Reymond Syahputra; Ramadhani, Zulfikar Ismaya (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2024)
Generation Z faces great challenges in maintaining healthy sleep patterns due to lifestyle changes and high exposure to technology. This study aims to identify the sleep patterns of Generation Z as well as the main factors that affect their sleep quality using the K-Means algorithm. Data was collected from 300 participants through an online questionnaire that included variables such as sleep duration, difficulty sleeping, caffeine consumption, electronic device use, physical activity, and freshness after waking up. With a clustering approach, the results of the study showed that there were three main patterns: irregular sleep patterns (45%), healthy sleep patterns (35%), and poor sleep patterns (20%). The cluster with healthy sleep patterns had an average of 7-8 hours of sleep, high physical activity, and low caffeine consumption, while irregular sleep patterns were less dominated by the use of electronic devices before bedtime, high caffeine consumption, and low physical activity. These findings highlight the importance of lifestyle management in improving the sleep quality of Generation Z and provide a basis for the development of more effective interventions. This study concludes that data-based clustering is a useful method to understand the sleep patterns of a particular population in more depth.